Identification of Immune Response to Sacbrood Virus Infection in Apis cerana Under Natural Condition - Deng, Yanchun; Zhao, Hongxia; Shen, Shuo; Yang, Sa; Yang, Dahe; Deng, Shuai; Hou, Chunsheng (Frontiers in Genetics, 2020)
Chinese sacbrood virus (CSBV) is a serious threat to eastern honeybees (Apis cerana), especially larvae. However, the pathological mechanism of this deadly disease remains unclear. Here, we employed mRNA and small RNA transcriptome approach to investigate the microRNAs (miRNAs) and small interfering RNAs (siRNA) expression changes of Apis cerana larvae infected with CSBV under natural condition. We found that serine proteases involved in immune response were down-regulated, while the expression of siRNAs targeted to serine proteases were up-regulated. In addition, CSBV infection also affected the expression of larvae cuticle proteins such as larval cuticle proteins A1A and A3A, resulting in increased susceptibility to CSBV infection. Together, our results provide insights into small RNAs that they are likely to be involved in regulating honeybee immune response.